Unveiling The Effectiveness of Instagram to Enhance Descriptive Text Writing - Rahayu, Nenden Sri; Rahayu, Yayu Sri; Ramadhani, Rizka Fauziah (English Education and Literature Journal (E-Jou), 2025)
This study investigates the effectiveness of Instagram as a tool for improving students' descriptive text writing skills. Conducted at SMPN 1 Cimaung from July 24 to August 10, 2023, the research involved 30 eighth-grade students. Using a pre-experimental design with a single group, the study assessed the impact of Instagram on students' writing performance through tests and questionnaires. The findings reveal a significant improvement in students' writing skills, with the t-test showing a higher value than the t-table (3.764 > 2.045). Additionally, 90% of students reported enjoying learning English, and 80% favored using Instagram for writing. These results suggest that Instagram is an effective tool for enhancing writing skills and engaging students in learning. This study not only adds to the growing body of research on digital tools in education but also provides practical insights into the integration of social media into language learning